Ghrelin regulates hyperactivity-like behaviors via growth hormone signaling pathway in zebrafish (Danio rerio) - Guan, Kaiyu; Shan, Chunyan; Guo, Anqi; Gao, Xiang; Li, Xi (Frontiers in Endocrinology, 2023)
Introduction Ghrelin is originally identified as the endogenous ligand for the growth hormone secretagogue receptor (GHSR) and partially acts by stimulating growth hormone (GH) release. Our previous studies have identified GHRELIN as a novel susceptibility gene for human attention-deficit hyperactivity disorder (ADHD), and ghrelin-depleted zebrafish (Danio rerio) display ADHD-like behaviors. However, the underlying molecular mechanism how ghrelin regulates hyperactivity-like behaviors is not yet known. Results Here, we performed RNA-sequencing analysis using adult ghrelinΔ/Δ zebrafish brains to investigate the underlying molecular mechanisms. We found that gh1 mRNA and genes related to the gh signaling pathway were significantly reduced at transcriptional expression levels. Quantitative polymerase chain reaction (qPCR) was performed and confirmed the downregulation of gh signaling pathway-related genes in ghrelinΔ/Δ zebrafish larvae and the brain of adult ghrelinΔ/Δ zebrafish. In addition, ghrelinΔ/Δ zebrafish displayed hyperactive and hyperreactive phenotypes, such as an increase in motor activity in swimming test and a hyperreactive phenotype under light/dark cycle stimulation, mimicking human ADHD symptoms. Intraperitoneal injection of recombinant human growth hormone (rhGH) partially rescued the hyperactivity and hyperreactive-like behaviors in ghrelin mutant zebrafish. Conclusion Our results indicated that ghrelin may regulate hyperactivity-like behaviors by mediating gh signaling pathway in zebrafish. And the protective effect of rhGH on ghrelinΔ/Δ zebrafish hyperactivity behavior provides new therapeutic clues for ADHD patients.